2012
DOI: 10.1212/wnl.0b013e31825dceca
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of major amyotrophic lateral sclerosis genes to the etiology of sporadic disease

Abstract: A considerable proportion of patients with SALS harbored mutations in major ALS genes. This result has relevant implications in clinical practice, namely in genetic counseling. The detection of double mutations in 2 patients raises the hypothesis that multiple mutations model may explain genetic architecture of SALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 39 publications
2
68
1
1
Order By: Relevance
“…The occurrence of mutations in more than one gene supports the idea that ALS could be considered an oligogenic disease, 30,35 with some of these genes displaying mendelian inheritance and a number of other genes acting as disease modifiers by influencing penetrance and pleiotropy. Indeed, in support of this view, C9orf72 repeat expansions have also been found to occur in Table 3 ATXN2 intermediary polyglutamine repeats co-occur with C9orf72 hexanucleotide repeat expansions patients carrying variants in a major ALS-or FTDcausing gene, such as TARDBP, SOD1, FUS, GRN, UBQLN2, OPTN, VAPB, and ANG.…”
Section: Figurementioning
confidence: 69%
See 1 more Smart Citation
“…The occurrence of mutations in more than one gene supports the idea that ALS could be considered an oligogenic disease, 30,35 with some of these genes displaying mendelian inheritance and a number of other genes acting as disease modifiers by influencing penetrance and pleiotropy. Indeed, in support of this view, C9orf72 repeat expansions have also been found to occur in Table 3 ATXN2 intermediary polyglutamine repeats co-occur with C9orf72 hexanucleotide repeat expansions patients carrying variants in a major ALS-or FTDcausing gene, such as TARDBP, SOD1, FUS, GRN, UBQLN2, OPTN, VAPB, and ANG.…”
Section: Figurementioning
confidence: 69%
“…20 Because of the presence of TDP-43 inclusions in many neurodegenerative diseases and the heterogeneity of their clinical presentation, a number of studies have evaluated ATXN2 repeat sizes in patients with neurodegenerative diseases. 17,[21][22][23][24][25][26][27][28][29][30][31][32][33] All the studies confirmed a significant association between intermediary repeat lengths and ALS, which is even stronger when familial cases are considered separately from sporadic cases. An association has also been found with PSP.…”
Section: Figurementioning
confidence: 70%
“…Since the first clinical study initiated in Ireland by Greenway et al [2], several SNPs encoding missense mutations in the coding region of ANG have been identified in ALS patients of Irish and Scottish background. Later studies confirmed the association of ANG mutations with ALS across diverse ethnic groups [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 86%
“…In all patients, ALS is thought to arise from a combination of genetic susceptibility (Renton, Chio et al 2014, Marangi and Traynor 25 Alruwaili thesis 2016 2015), and environmental exposure (Fang, Kamel et al 2009), and may be due to a multi-stage process (Al-Chalabi, Calvo et al 2014). Causative genes have been identified in fALS, with some of these genetic mutations also found in patients with sporadic ALS (sALS) (Lattante, Conte et al 2012). It has been estimated that 61% of the variance in risk of developing sALS is due to genetic factors (Al-Chalabi, Fang et al 2010).…”
Section: List Of Supplementary Tablesmentioning
confidence: 99%